Pengembangan Kapasitas Organisasi dalam Peningkatan Kualitas Pelayanan Publik Dinas Kehutanan dan Perkebunan Kabupaten Bone - Ashar Prawitno; Andi Samsu Alam (Departemen Ilmu Pemerintahan Fisip Unhas, 2015)
Abstract: The purposes of this research are to explain the development of organizational capacity in improving the quality of public services in the forestry and plantation office of Bone regency and explain the steps conducted by the office in developing its organizational capacity by focus on three aspect: the devolopment of phiysical resources, the development of operational processes, and the development of human resources. It is found that: (1) the development of the capacity of physical resources, in general, is quite good, as it is shown by some indicators including physical resuorces, organizational structure, financial matters, legal instruments(rules), and facilities and infrastructure; (2) the development of operational process (management) capacity is generally good, the indicators are work procedures, work culture, and leadership; (3) the development of human resource capacity. The indicators are knowledge of employees, skills of employees, and work attitude and ethic. Keywords: capacity development, organizations, public service Abstrak: Penelitian ini bertujuan untuk menjelaskan pengembangan kapasitas organisasi dalam peningkatan kualitas pelayanan publik pada Dinas Kehutanan dan Perkebunan Kabupaten Bone dan menjelaskan langkah-langkah yang ditempuh Dinas Kehutanan dan Perkebunan Kabupaten Bone dalam pengembangan kapasitas organisasi pemerintahnya guna peningkatan kualitas pelayanan publik yang difokuskan pada tiga aspek yaitu pengembangan sumber daya fisik, pengembangan proses operasional dan pengembangan sumber daya manusia. Hasil temuan dari penilitian diketahui: (1) pengembangan kapasitas sumber daya fisik secara umum cukup baik, indikatornya yaitu sumber daya fisik, struktur organisasi, keuangan, perangkat hukum (aturan), dan sarana dan prasarana, hanya satu indikator yang mendapat penilaian kurang baik, yaitu kapasitas perangkat hukum; (2) pengembangan kapasitas proses operasional (ketatalaksanaan) secara umum baik dengan indikatornya yaitu prosedur kerja, budaya kerja, dan kepemimpinan; (3) pengembangan kapasitas sumber daya manusia, indikatornya yaitu pengetahuan pegawai, keterampilan pegawai, serta perilaku dan etika kerja. Kata kunci : pengembangan kapasitas, organisasi, pelayanan publik